CD74 in Kidney Disease - Valiño-Rivas, Lara; Baeza-Bermejillo, Ciro; Gonzalez-Lafuente, Laura; Sanz, Ana Belen; Ortiz, Alberto; Sanchez-Niño, Maria Dolores (Frontiers in Immunology, 2015)
CD74 (invariant MHC class II) regulates protein trafficking and is a receptor for macrophage migration inhibitory factor (MIF) and D-dopachrome tautomerase (D-DT/MIF-2). CD74 expression is increased in tubular cells and/or glomerular podocytes and parietal cells in human metabolic nephropathies, polycystic kidney disease, graft rejection and kidney cancer and in experimental diabetic nephropathy and glomerulonephritis. Stressors like abnormal metabolite (glucose, lyso-Gb3) levels and inflammatory cytokines increase kidney cell CD74. MIF activates CD74 to increase inflammatory cytokines in podocytes and tubular cells and proliferation in glomerular parietal epithelial cells and cyst cells. MIF overexpression promotes while MIF targeting protects from experimental glomerular injury and kidney cysts, and interference with MIF/CD74 signaling or CD74 deficiency protected from crescentic glomerulonephritis. However, CD74 may protect from interstitial kidney fibrosis. Furthermore, CD74 expression by stressed kidney cells raises questions about the kidney safety of cancer therapy strategies delivering lethal immunoconjugates to CD74-expressing cells. Thus, understanding CD74 biology in kidney cells is relevant for kidney therapeutics.